Laughter and Well-being: The Transformative Experiences of Working Mothers - Jhonna G. Toledo; Araceli C. Doromal (Philippine Social Science Journal, 2025)
Addressing the intense pressures faced by working mothers, this descriptive phenomenological study explores the transformative impact of laughter therapy on stress, resilience, and overall well-being. Through in-depth interviews with six practitioners from the Adventist women's ministry, the research identified laughter—whether genuine or simulated—as a holistic intervention that significantly improves physical health, psychological resilience, interpersonal bonds, and spiritual connection. These findings posit laughter therapy as a versatile, accessible tool for workplace and community application, while suggesting that future research should compare its efficacy against other interventions and examine its effects across diverse demographics and cultural contexts.